Design and Analysis of Fractal Antenna for ISM Band Application - R., Praveena; S.G., Boopathi; K., Karthi; K., Krishnan (IRO Journal on Sustainable Wireless Systems, 2025)
The research presents the design and analysis of a compact fractal antenna optimized for ISM band applications at operating frequencies of 2.4 GHz and 5.8 GHz. The proposed antenna utilizes a self-similar fractal geometry with overall dimensions of just 10 mm × 10 mm, making it highly suitable for space-constrained wireless devices such as IoT modules, RFID systems, and wearable technology. The feed-line width is precisely optimized at 0.50 mm to ensure effective impedance matching and minimal signal loss. Performance analysis, conducted using CST Microwave Studio, reveals a return loss (S11) of less than -10 dB and a Voltage Standing Wave Ratio (VSWR) ranging approximately between 1 and 2, indicating efficient signal transmission with minimal reflection. Furthermore, the antenna achieves a gain between 3 dBi and 6 dBi, demonstrating strong radiation characteristics suitable for reliable short-range to mid-range communication. The results confirm the capability of the proposed fractal antenna as a compact, efficient, and multi-band solution for modern wireless communication systems.